Porównanie wyników fakoemulsyfikacji zaćmy o różnym stopniu stwardnienia jądra soczewki i bezpieczeństwa jej wykonania - Laudańska-Olszewska, Iwona; Synder, Aleksandra; Wesołek-Czernik, Agata; Omulecki, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To compare the course of surgery and operative outcomes in patients with different stages of nuclear hardness. Material and methods: The study comprises 36 patients with hard nucleus cataract (III and IV degree in LOCS scale) – group II and 45 patients with softer types of cataract (I and II degree in LOCS scale) – group I. All patients underwent clear corneal phacoemulsification and foldable intraocular lens implantation. In both groups intraoperative course was assessed and energy with effective phaco time were measured. Visual acuity, intraocular pressure, central corneal thickness and endothelial cell density were estimated preoperatively and one week postoperatively. Results: Energy and effective phaco time were significantly higher in group II. Mean visual acuity in both groups was 0.8 ± 0.2. Intraocular pressure, central corneal thickness and endothelium cell loss were not significantly different in both groups. Endothelium cell loss were not significantly correlated with increase of energy or duration of phacoemulsification in any of groups. Conclusions: Cataracts with higher stage of nuclear hardness required more energy and effective phaco time to be employed, but it did not influenced significantly postoperative visual acuity, intraocular pressure, central corneal thickness change and loss of endothelial cells.